2013
DOI: 10.4028/www.scientific.net/amr.747.367
|View full text |Cite
|
Sign up to set email alerts
|

Biocomposites from Cassava Pulp/Polylactic Acid/Poly(butylene Succinate)

Abstract: In this study, effect of PBS content on physical properties of polylactic acid (PLA) and polybutylene succinate (PBS) blends was studied. The content of PBS was varied from 0 30 %wt. The blends were mixed using an internal mixer. The samples were prepared using a compression molding. It was shown that tensile strength and Youngs modulus of PLA/PBS blends were decreased with increasing PBS content from to 0 30 %wt. Nevertheless, elongation at break and impact strength of the blend were increased with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…With 10 wt.% of compatibilizer, the viscosity of the PBAT/PLA blend increased, and there was no longer a crystalline region of PBAT, showing an improved compatibility of PLA and PBAT. PLA/cassava pulp/PBS ternary biocomposites were also compatibilized by PLA-g-GPA, with the mechanical properties of the PLA/cassava pulp/PBS composites being improved with the addition of PLA-g-GMA [80]. Similar to polyesters, PLA/thermoplastic polyurethane (TPU) blends were also compatibilized in the presence of PLA-g-GMA [81].…”
Section: Pla-g-polyestersmentioning
confidence: 99%
See 1 more Smart Citation
“…With 10 wt.% of compatibilizer, the viscosity of the PBAT/PLA blend increased, and there was no longer a crystalline region of PBAT, showing an improved compatibility of PLA and PBAT. PLA/cassava pulp/PBS ternary biocomposites were also compatibilized by PLA-g-GPA, with the mechanical properties of the PLA/cassava pulp/PBS composites being improved with the addition of PLA-g-GMA [80]. Similar to polyesters, PLA/thermoplastic polyurethane (TPU) blends were also compatibilized in the presence of PLA-g-GMA [81].…”
Section: Pla-g-polyestersmentioning
confidence: 99%
“…A PLA-g-PAA copolymer is formed, which can then react with alcohol functions of the cellulosic derivatives by esterifying the alcohol functions of the cellulosic compound (Figure 16). PLA/cassava pulp/PBS ternary biocomposites were also compatibilized by PLA-g-GPA, with the mechanical properties of the PLA/cassava pulp/PBS composites being improved with the addition of PLA-g-GMA [80]. Similar to polyesters, PLA/thermoplastic polyurethane (TPU) blends were also compatibilized in the presence of PLA-g-GMA [81].…”
Section: Pla-g-acrylic Acid (Pla-g-aa)mentioning
confidence: 99%
“…Another research reported the inclusion of the PLA-g-GMA as compatibilizer to cassava pulp/poly(lactic acid)/poly(butylene succinate) blend composites that improved the impact strength. 119 Yao et al 90 reported the RS fiber (900-1200 mm) reinforced HDPE composite by investigating the effect of various compatibilizers. The Izod impact strength (ASTM D256) improved the most with the use of 4.3% PE-g-MA treatment (þ67%), followed by 4.3% EPR-g-MA (þ60%) and 4.3% uPER (þ48%) with respect to the unmodified HDPE/RS.…”
Section: Impact Testingmentioning
confidence: 99%
“…The modification of PLA by the addition of plasticizers, nonbiodegradable, and biodegradable fillers is a well‐known procedure for improving the PLA properties . Cellulose ester, citric acid, glycidyl methacrylate, and poly(ethylene glycol) (PEG) are widely used plasticizers for PLA. For example, PLA containing PEG plasticizer exhibited greater enzymatic degradation than neat PLA .…”
Section: Introductionmentioning
confidence: 99%